Is transvaginal natural orifice transluminal endoscopic surgery (vNOTES) indicated in patients with previous extensive pelvic surgeries? A case report - Yannick Hurni; Fabien Romito; Daniela Emanuela Huber (Elsevier, 2022)
Transvaginal natural orifice transluminal endoscopic surgery (vNOTES) has been increasingly applied to perform multiple gynecologic procedures. However, evidence is lacking on whether this surgical approach is feasible for patients with prior extensive abdominopelvic surgeries.We report a case of prophylactic bilateral salpingo-oophorectomy (BSO) performed in a 51-year-old patient with previous laparotomic radical hysterectomy and pelvic lymphadenectomy for cervical cancer. The patient underwent rectovaginal examination and evaluation of the transvaginal sonographic sliding sign as preoperative screening to exclude the obliteration of the pouch of Douglas. The abdominal cavity was accessed by cautious endoscopic access to the pouch of Douglas. The BSO was realized in accordance with risk-reducing surgery guidelines. No intraoperative or postoperative complications were observed.We suggest that selecting patients carefully prior to operation and adapting intraoperative techniques could be a safe method for conducting vNOTES interventions in patients with extensive abdominopelvic adhesions.